Acute Melatonin Administration in Humans Impairs Glucose Tolerance in Both the Morning and Evening - Rubio-Sastre, Patricia (Associated Professional Sleep Societies, LLC, 2014)
STUDY OBJECTIVES: To study the effect of melatonin administration on glucose metabolism in humans in the morning and evening. DESIGN: Placebo-controlled, single-blind design. SETTING: Laboratory assessments. PARTICIPANTS: 21 healthy women (24 ± 6 y; body mass index: 23.0 ± 3.3 kg/m(2)). INTERVENTIONS: Glucose tolerance was assessed by oral glucose tolerance tests (OGTT; 75 g glucose) on 4 occasions: in the morning (9 AM), and evening (9 PM); each occurring 15 minutes after melatonin (5 mg) and placebo administration on 4 non-consecutive days. MEASUREMENTS AND RESULTS: Melatonin administration impaired glucose tolerance. When administered in the morning, melatonin significantly increased the incremental area under the curve (AUC) and maximum concentration (Cmax) of plasma glucose following OGTT by 186% and 21%, respectively, as compared to placebo; while in the evening, melatonin significantly increased glucose AUC and Cmax by 54% and 27%, respectively. The effect of melatonin on the insulin response to the OGTT depended on the time of day (P < 0.05). In the morning, melatonin decreased glucose tolerance primarily by decreasing insulin release, while in the evening, by decreasing insulin sensitivity. CONCLUSIONS: Acute melatonin administration in humans impairs glucose tolerance in both the morning and evening. When administering melatonin, the proximity to meal timing may need to be considered, particularly in those at risk for glucose intolerance. CITATION: Rubio-Sastre P, Scheer FA, Gómez-Abellán P, Madrid JA, Garaulet M. Acute melatonin administration in humans impairs glucose tolerance in both the morning and evening. SLEEP 2014;37(10):1715-1719.